2010
DOI: 10.1038/gene.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

New genetic associations detected in a host response study to hepatitis B vaccine

Abstract: The immune response to hepatitis B vaccination differs greatly among individuals, with 5-10% of healthy people failing to produce protective levels of antibodies. Several factors have been implicated in determining this response, chiefly individual genetic variation and age. Aiming to identify genes involved in the response to hepatitis B vaccination, a two-stage investigation of 6091 single-nucleotide polymorphisms (SNPs) in 914 immune genes was performed in an Indonesian cohort of 981 individuals showing nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 41 publications
1
50
1
1
Order By: Relevance
“…Additionally, immunogenetic studies have also shown associations between polymorphisms in gene-encoding immune response proteins and variation in response to vaccines. Among others, associations between an SNP in the forkhead box protein 1 (FOXP1) gene, a transcription factor regulating B cell development (25) and in various cytokine genes, such as gamma interferon (IFN-␥), IL-4, IL-4R, IL-10, IL-10RA, IL-12B, and tumor necrosis factor (TNF), and the vaccine efficacy have also been shown (26,27). Another proposed inhibitory mechanism that may contribute to inadequate infant response to vaccine is related to high titers of maternal antibodies that persist over a period of 6 to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, immunogenetic studies have also shown associations between polymorphisms in gene-encoding immune response proteins and variation in response to vaccines. Among others, associations between an SNP in the forkhead box protein 1 (FOXP1) gene, a transcription factor regulating B cell development (25) and in various cytokine genes, such as gamma interferon (IFN-␥), IL-4, IL-4R, IL-10, IL-10RA, IL-12B, and tumor necrosis factor (TNF), and the vaccine efficacy have also been shown (26,27). Another proposed inhibitory mechanism that may contribute to inadequate infant response to vaccine is related to high titers of maternal antibodies that persist over a period of 6 to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The 6p21-22 region, harboring human major histocompatibility complex (MHC), also showed an overrepresentation of African ancestry in this study (although <3 SD) and has been reported under selection in various studies (Garrigan and Hedrick 2003;Tang et al 2007). MUC1, located in 1q22, is involved in signaling by PDGF and serves a protective function by binding to pathogens (Davila et al 2010;Li et al 2010). HBB and HBD, located in 11p15, have been subjected to balancing selections because their mutations protected against malaria according to numerous studies (Ashley-Koch et al 2000;Wood et al 2005).…”
Section: Natural Selection In African Americansmentioning
confidence: 99%
“…ITGAL forms a subunit of lymphocyte function-associated antigen-1 (LFA1), together with ITGB2, and plays a central role in immune cell interaction by binding to ICAMs and regulating leukocyte-endothelial cell interaction, cytotoxic T-cell mediated killing, and antibody dependent killing by granulocytes and monocytes. The largest study in this field to date is that by Davila et al (Davila et al, 2010), and comprised a two-stage screen of just under 6000 SNPs in over 900 immune genes with regard to HBV vaccine failure following a two-dose immunisation schedule in 981 Indonesians. Non-response was shown to be associated with SNPs in BTNL2, IL6ST, KLRF1, LY6H, MBL2, TGFB3, HLAB, HLA-DRA, HLA-DRQB1, FOXP1, LILRB4, TGFB2, TNFSF15, C5, CCL15, with the most convincing evidence for MHC genes and the latter six genes listed.…”
Section: Genetics Of Immunity Induced By Hbv Vaccinationmentioning
confidence: 99%